Supplementation with Red Palm Oil Increases β-Carotene and Vitamin A Blood Levels in Patients with Cystic Fibrosis - Olaf Sommerburg; Silke De Spirt; Annett Mattern; Cornelia Joachim; Claus-Dieter Langhans; Kalanithi Nesaretnam; Werner Siems; Wilhelm Stahl; Marcus A. Mall (Mediators of Inflammation)
Patients with cystic fibrosis (CF) show decreased plasma concentrations of antioxidants due to malabsorption of lipid soluble vitamins and consumption by chronic pulmonary inflammation. β-Carotene is a major source of retinol and therefore is of particular significance in CF. The aim of this study was to investigate the effect of daily intake of red palm oil (RPO) containing high amounts of β-carotene on the antioxidant levels in CF patients. Sixteen subjects were recruited and instructed to enrich their food with 2 to 3 tablespoons of RPO (~1.5 mg of β-carotene) daily over 8 weeks. Carotenoids, retinol, and α-tocopherol were measured in plasma at baseline and after intervention. In addition β-carotene, lycopene, α-tocopherol, and vitamin C were measured in buccal mucosa cells (BMC) to determine the influence of RPO on antioxidant tissue levels. Eleven subjects completed the study properly. Plasma β-carotene, retinol, and α-carotene of these patients increased, but plasma concentrations of other carotenoids and α-tocopherol as well as concentrations of β-carotene, lycopene, α-tocopherol, and vitamin C in BMC remained unchanged. Since RPO on a daily basis did not show negative side effects the data suggest that RPO may be used to elevate plasma β-carotene in CF.